Progress and Challenges of Upper Secondary Education in China - Chen, Dandan (World Bank, Washington, DC, 2019)
Over the past decade, China’s transition rate from lower secondary education to higher secondary education has increased significantly, from 80.5 to 93.7 percent. In light of this impressive progress, the Chinese government aimed at raising the gross enrollment rate in senior high schools to above 90 percent by 2020. Quality and relevance in vocational and academic high school education could be a key bottleneck in further expansion. The way tracking operates between academic and vocational streams could itself be a distortion for the sector’s further expansion. Looking ahead, reforms in upper secondary education are imperative, given increasing demand for a highly skilled labor force and China’s fast demographic change as the young population cohorts decline. The paper examines the sector’s key constraints in access, financing, tracking, and informed decisions and recommends how the quality of the general and vocational education tracks can be further improved.